2016
DOI: 10.1002/tkm2.1056
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of Kampo therapy

Abstract: Aim: The aim of this study was to investigate the current circumstances of pharmacoeconomic evaluation of Kampo therapy, by carrying out qualitative analysis of articles on the economic evaluation of Kampo therapy published over the last 30 years from an evidence-based medicine viewpoint. Methods: The Japan Medical Abstracts Society (JAMAS) Web Ver. 5 was searched for reports relevant to cost-effectiveness evaluation in Japan published between 1983 and 2013. Search terms used were 'Kampo', 'economics', and 'co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It not only helps reduce the number of drugs but also improves subjective symptoms and maintains a high quality of life . The possibility of reducing pharmaceutical costs by using kampo medicine has already been noted , but reports of a 10 year observation on a patient are rare. The total pharmaceutical cost for the present patient when receiving the 13 drugs was ¥461.3 per day, but it was reduced to ¥165.3 per day after stabilization with kampo medicine, indicating a pharmaceutical cost reduction of ¥296 per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It not only helps reduce the number of drugs but also improves subjective symptoms and maintains a high quality of life . The possibility of reducing pharmaceutical costs by using kampo medicine has already been noted , but reports of a 10 year observation on a patient are rare. The total pharmaceutical cost for the present patient when receiving the 13 drugs was ¥461.3 per day, but it was reduced to ¥165.3 per day after stabilization with kampo medicine, indicating a pharmaceutical cost reduction of ¥296 per day.…”
Section: Discussionmentioning
confidence: 99%
“…Because a single prescription of kampo medicine can be expected to have various effects, there is a possibility to achieve reduction in the number and cost of drugs with this medicine. A recent review suggested that kampo medicine has been reducing pharmaceutical costs already . In this report, we present one case of kampo therapy with a long‐term follow‐up observation period and describe the effect of this treatment on daily drug regimen and cost.…”
Section: Introductionmentioning
confidence: 94%